2016
DOI: 10.2217/nnm-2016-0062
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluation of gold-DTDTPA Nanoparticles As Theranostic Agents in Prostate Cancer Radiotherapy

Abstract: This study demonstrates the potential of Au@DTDTPA to enhance CT-image contrast and simultaneously increases the radiosensitivity of prostate tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…Gold nanoparticles are being explored in many applications in the biomedical field such as contrast agents for medical imaging 11,14 , drug delivery, targeted killing of cells 21 and also therapeutic applications, such as theranostic agents 37 and radiosensitization 38 . This has led to numerous investigations of their toxicity and biodistribution.…”
Section: Resultsmentioning
confidence: 99%
“…Gold nanoparticles are being explored in many applications in the biomedical field such as contrast agents for medical imaging 11,14 , drug delivery, targeted killing of cells 21 and also therapeutic applications, such as theranostic agents 37 and radiosensitization 38 . This has led to numerous investigations of their toxicity and biodistribution.…”
Section: Resultsmentioning
confidence: 99%
“…Au nanoparticle was also studied as a drug-delivery platform in transient anti-angiogenic therapies to induce tumour vascular normalization and enhance the efficacy of the cytotoxic drugs[15]. Moreover, tumour radiosensitizations for breast and prostate with Au nanoparticle addition were studied both in vitro and in vivo based on the cell-line and small-animal model[16,17]. …”
Section: Introductionmentioning
confidence: 99%
“…This data is shown in Figure 8 (red squares) and was generated using Clonogenic survival assays following treatment with 0-6 Gray (Gy) 160 kVp x-rays as previously described by Butterworth et al [18]. The survival fractions were calculated as the plating efficiency of the treated group divided by the plating efficiency of the untreated control cells, with error bars representing the standard deviation (SD) (n = 7).…”
Section: Comparison With Wet Laboratory Survival Fraction Resultsmentioning
confidence: 99%
“…The wet laboratory experiments had duration of twelve days and initial populations of 200 to 600 cells. Previously, Butterworth et al [18] showed that all damage to cells would take place within 48 hours (2 days); however, twelve days are required for observable colonies to form. The advantage of computational modelling is that the results can be observed at 48 hours and assumptions made that if cells have survived to 48 hours then they will form colonies by 12 days.…”
Section: Comparison With Wet Laboratory Survival Fraction Resultsmentioning
confidence: 99%